Analysis productivity of seaweed cultivation (Glacilaria. sp) in Takalar Regency, South Sulawesi. Issue 1 (April 2020) - Riskiyani,; Adhawati, S S; Fudjaja, L
Abstract: Seaweed is one of the leading commodities that has enormous potential supported by sea area of 5.8 million km 2 with a total area of seaweed cultivation reaching 1.110.900 ha. One type of kelp cultured in ponds is Glacilaria sp. Seaweed production is a strategic step at the level of crop development as it involves a high workload, a simple growing technology, a relatively short planting time of about 45 days (fast yield), and relatively cheap production costs. The increasing demand for seaweed from year to year is not followed by an increase production volumes and fluctuating prices. The purpose of this research is to determine the description of the agrifood subsystem and to determine the productivity of the seaweed company Glacilaria sp. in the regency of Takalar. The design of the research used qualitative and quantitative types. The number of samples used was 63 people. The results of this study were to look at the productivity of the seaweed cultivation of Glacilaria sp. The productivity in the Mappakasunggu District was 1.37, while the productivity in the Sanrobone District was 1, 43. Good productivity, namely the use of inputs, is less than the output results obtained so that the income of fishers who cultivating seaweed Glacilaria sp. is more increasing.